Darcy-Forchheimer flow of radiative carbon nanotubes with microstructure and inertial characteristics in the rotating frame. (September 2018) - Shah, Zahir; Dawar, Abdullah; Islam, Saeed; Khan, Ilyas; Ching, Dennis Ling Chuan
Abstract: The current study deals with Darcy-Forchheimer three-dimensional micropolar rotational nanofluid flow of single wall and multiwall carbon nanotubes base on the fluids (water, engine oil, ethylene glycol and kerosene oil). The nanofluid flow are examined between parallel and horizontal plates in a rotating system. The micropolar nanofluid in permeable media is designated by assuming the Darcy-Forchheimer model where drenching permeable space obeys the Darcy-Forchheimer expression. The thermal radiation impact is taken to be varying in the absorption/generation for the purpose, to see the concentration as well as the temperature modifications between the nanofluid and the surfaces. The impacts of the porosity, rotation and inertia coefficient analysis have been mainly focused in this research. Plots have been presented in order to examine how the velocities and temperature profile get affected by various flow parameters. The leading equations are converted to a system of differential nonlinear equations and then homotopic method has been used for solution.